Speciation and total determination of arsenic, chromium and selenium in freshwater bodies sediment - Abdullah Salim, Nazaratul Ashifa (2009)
Arsenic (As) is generally known for its toxicity while chromium (Cr) and selenium (Se) at the appropriate amount are essential elements to man and becomes quite toxic in excessive amount. Anthropogenic activities such as industrialization, agricultural and urbanization have led to the contamination of toxic elements into aquatic that finally end up in the sediment system. Environmental process such as diagenetic process causes the toxic elements to migrate from the bedrock materials into the sediment surface and lastly into the water column. This process has been recognized to be the factor of As contamination in well water in several countries such as Bangladesh, Taiwan, USA and Canada. A number of samples of freshwater sediments from identified rivers and lakes in Johor Bharu area had been analyzed to determine the concentration level of As, Cr and Se using neutron activation analysis (NAA) technique. Certified reference material (CRM) namely IAEA Soil-7, Marine Sediment Reference Material BCSS-1 and PACS -2 were applied to provide good quality assurance control during analysis. The results obtained show that the concentrations of As in the rivers and lakes sediment fall between 10 to 34 ^g g"1 and 18 to 62 ^g g"1, respectively. The concentrations of Cr in the rivers ranged between 27 ^g g"1 to 125 ^g g"1, while in the lake sediments the concentrations ranged between 173 ^g g"1 to 301 ^.g g"1. The river sediment showed the Se concentration ranged between 0.56 ^g g"1 to 1.91 ^g g"1 and in lake sediment the concentration ranged between 0.31 ^g g"1 to 1.08 ^g g"1. The results of the As, Cr and Se concentrations were then compared to the ‘background value’ proposed by National Oceanic and Atmospheric Administration (NOAA), USA and several sediment quality guidelines. The As, Cr and Se concentrations were also correlated and normalized to iron content in order to evaluate and estimate the degree of contaminant enrichment in sediments. For speciation study, the inorganic species of As(III), As(V), Se(IV) and Se(VI) were studied by extracting the sediments using the microwave at the optimized time and power setting in the mild concentration of acid media. The As(III) and As(V) were preconcentrated and separated by ammonium pyrolidinedithiocarbamate (APDTC) into methyl isobuthyl ketone (MIBK) while the Se(IV) and Se(VI) were separated after co"precipitation of sodium dibenzyldithiocarbamate (Na"DBDTC) with phenolphthalein. The efficiencies of all extraction procedures were determined using standard solutions and several CRM. The results showed that As(V) and Se(VI) were the dominant species in the river and lake sediments.